Solvent Extraction of Chromium(VI) from Othophosphoric and Perchloric Acid Solutions by Triphenylphosphine Oxide - HARIHARAN, A.V.L.N.S.H. (Asian Journal of Chemistry, 2010)
The extraction of chromium(VI) from orthophosphoric and perchloric acid solutions with triphenylphosphine oxide has been studied. The optimum conditions for extraction were established from the study of the effect of serveral variables like-concentration of phosphine oxide, metal ion, acidity, foreign ions etc. The extractions are nearly quantitative from orthophosphoric acid and are partial from perchloric acid solutions. The extracted species are identified. Estimation of chromium content in industrial effluents and synthetic samples has been attempted.